Emerging Market Corporate Leverage and Global Financial Conditions - Alter, Adrian (IMF Working Papers; Working Paper, 2016)
Corporate debt in emerging markets has risen significantly in recent years amid accommodative global financial conditions. This paper studies the relationship of leverage growth in emerging market (EM) firms to U.S. monetary conditions, and more broadly, to global financial conditions. We find that accommodative U.S. monetary conditions are reliably associated with faster EM leverage growth during the past decade. Specifically, a 1 percentage point decline in the U.S. policy rate corresponds to an appreciable increase in EM leverage growth of 9 basis points, on average (relative to the sample average leverage growth of 35 basis points per year). This impact is more pronounced for sectors dependent on external financing, for SMEs, and for firms in more financially open EMs with less flexible exchange rates. The findings suggest that global financial conditions affect EM firms' leverage growth in part by influencing domestic interest rates and by relaxing corporate borrowing constraints.